Eustra yinggelingensis sp. nov., a new flanged bombardier beetle from Yinggeling Nature Reserve, Hainan, China with contribution to the knowledge of Chinese Eustra species (Coleoptera, Carabidae, Paussinae) - Jiang, Ri-Xin; Wang, Cheng-Bin; Mi, Hong-Xu; Wang, Shuo (Zootaxa, 2019)
A new species of flanged bombardier beetle form Hainan Island, China, Eustra yinggelingensis sp. nov. (Coleoptera, Carabidae, Paussinae, Ozaenini) is described. The new species was collected in rotten wood from Yinggeling Nature Reserve. Habitus and diagnostic features of the new species are illustrated. List, key and distribution map of all known Chinese Eustra species are given.